Movements of marked Sea and Diving Ducks in Europe - Boyd, Hugh (Wildfowl, 1959)
Ringing of dabbling ducks in Europe has helped considerably in discovering the patterns of their distribution and movement through the year. By comparison our knowledge of the behaviour of British species of the tribes Aythyini and Mergini is meagre, chiefly because they are harder to catch outside the breeding season. The numbers marked in Britain have been small, and seem unlikely to be rapidly increased, but ringers in some countries where these ducks breed more plentifully have marked considerably more. Captures of adults, mostly females taken on the nest, have been particularly informative. This paper reviews the results so far apparent. It is based on published and unpublished British records, and on the published material of foreign ringing schemes.